2015
DOI: 10.1007/s00246-015-1245-y
|View full text |Cite
|
Sign up to set email alerts
|

IL10 Promoter Polymorphisms are Associated with Rheumatic Heart Disease in Saudi Arabian Patients

Abstract: Rheumatic heart disease (RHD) is an inflammatory disease that develops following streptococcal infections. IL10 helps to balance immune responses to pathogens. IL10 polymorphisms have been associated with RHD, although results remain inconclusive. Our aim was to investigate the association between IL10 polymorphisms and RHD in Saudi Arabian patients. IL10 promoter polymorphisms (-1082A/G, -829C/T, and -592C/A) were genotyped in 118 RHD patients and 200 matched controls using the TaqMan allelic discrimination a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…The patient and control cohorts are described in previous studies ( 15 , 16 ). Briefly, diagnosis was made according to the modified Jones criteria at initial diagnosis and confirmed by echocardiography ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…The patient and control cohorts are described in previous studies ( 15 , 16 ). Briefly, diagnosis was made according to the modified Jones criteria at initial diagnosis and confirmed by echocardiography ( 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…Pooled analysis of five studies reporting on the IL‐10 ‐1082G>A (rs1800896) showed no association between RHD in 638 cases and 690 healthy controls (Muhamed, Engel, Shaboodien, Pare, & Mayosi, ). Among the five studies, two studies from Egypt and Saudi Arabia found an association between the IL‐10 (‐1082G>A, rs1800896) SNP and RHD (Abdallah, Alnuzha, et al, ; Settin et al, ), contrary to four studies from Pakistan, Egypt, and Indian (Gupta et al, ; Poomarimuthu et al, ; Rehman et al, ; Yousry et al, ).…”
Section: Resultsmentioning
confidence: 93%
“…A total of 96 articles were retrieved, after layer by layer screening, the final 3 case control studies were included [ 28 30 ], including three English literatures and 0 Chinese literatures. A total of 318 patients with rheumatic heart disease and 502 control subjects, literature screening process and results are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Related research [ 43 , 44 ] pointed out that the increase of IL-10 expression in the serum of patients with rheumatic heart disease is closely related to the occurrence and progression of the disease, and with the increase of the level of IL-10 expression, the worse the prognosis, the higher the mortality rate. Abdallah [ 30 ] study showed that the effect of IL-10 on the role of 1082G/A in patients with rheumatic heart disease is related to the single nucleotide polymorphisms (SNPs) in the gene promoter region. GG+GA gene polymorphism significantly increases the incidence of rheumatic heart disease in the population, AA gene polymorphism significantly reduces the incidence of rheumatic heart disease in the population, but the conclusion is still not uniform.…”
Section: Discussionmentioning
confidence: 99%